Adoption Of Environmental, Social, And Governance (ESG) Practices In Small Manufacturing In India - Jain, Amit (Digital Repository of Theses, 2025)
This study explores the adoption of Environmental, Social, and Governance (ESG) practices within small and medium-sized enterprises (SMEs) in India’s manufacturing sector. Amidst rising global attention to sustainable practices, Indian SMEs face mounting pressure to align with ESG standards despite facing systemic constraints. The research employs a Quantitative approach—surveys to assess current ESG adoption levels, identify motivating factors, barriers, and institutional influences. Findings reveal that environmental initiatives are more commonly implemented than social and governance components, primarily due to cost-savings and international client requirements. Key drivers include global supply chain integration and reputationbuilding, while barriers such as financial constraints, technical knowledge gaps, and minimal policy outreach limit progress. This dissertation contributes to stakeholder theory and resource-based view by contextualizing ESG within the Indian SME ecosystem. The research offers policy recommendations and practical pathways to scale ESG practices among SMEs for sustainable economic development.